2008
DOI: 10.1063/1.3052923
|View full text |Cite
|
Sign up to set email alerts
|

A slip model for rarefied gas flows at arbitrary Knudsen number

Abstract: A slip model for wall bounded rarefied gas flows is derived from kinetic theory. A corresponding modified Reynolds lubrication equation is obtained from the slip velocity boundary conditions at walls for high Knudsen number gas flows. The slip model in a simplest form has predictions very close to the numerical solutions of linearized Boltzmann equation in the whole Knudsen number range, and is preferable to the widely applied 1st order (Maxwell slip model), 2nd order, and 1.5 order slip models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(138 citation statements)
references
References 5 publications
2
135
0
1
Order By: Relevance
“…From the above examples of the velocity and shear stress profiles, it is seen that the combination of the two slip parameters and the mass transfer can greatly change the fluid flow and the shear stresses on the sur-face and in the fluid. The introduction of the secondorder slip parameter can increase the wall slip velocity and reduce the wall drag, which is a better match to the real flow physics compared with the previous velocity slip models [21].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…From the above examples of the velocity and shear stress profiles, it is seen that the combination of the two slip parameters and the mass transfer can greatly change the fluid flow and the shear stresses on the sur-face and in the fluid. The introduction of the secondorder slip parameter can increase the wall slip velocity and reduce the wall drag, which is a better match to the real flow physics compared with the previous velocity slip models [21].…”
Section: Resultsmentioning
confidence: 92%
“…However, in these papers, only first-order Maxwell slip conditions were used. Recently, Wu [21] proposed a new secondorder slip velocity model which matches better with the Fukui-Kaneko results based on the direct numerical simulation of the linearized Boltzmann equation [22]. Most recently, this new slip model was applied to the flow over a shrinking sheet and significantly different flow behaviour was found compared with the firstorder slip velocity [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beskok and Karniadakis (1999) suggested an improved second-order slip condition. For more details, readers are encouraged to read the papers by Srikanth (1969) and Wu (2008). Recently, Fang et al (2010) considered the effects of the second-order slip on the flow of a shrinking sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the slip function yields liquid holdup and pressure drop with an average absolute error of 17% and 19.5% whereas the error for double slit model is 20% and 18%. Wu (2008) present a slip model for rarefied gas flows at arbitrary Knudsen number. studied viscous flow over a shrinking sheet with a second order slip flow model.…”
Section: Introductionmentioning
confidence: 99%